The attitude, belief, support and knowledge level of the youth and their acceptance towards agriculture contract farming - Uli, Jegak; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman (Science Publications, 2010)
Problem statement: Agriculture sector in Malaysia has been intensified through the Eight and Ninth Malaysian Plan. In order to further develop this sector, contract farming activities such as leech rearing, worm rearing, herbs and mushroom have been introduced to the community. But do the communities especially the youth have a positive acceptance towards this activity? Approach: This was a quantitative study. The respondents were among two agriculture learning institutions in Malaysia. From a simple random sampling, a total of 194 respondents were selected. The data collection took two months to be completed. Results: From the multiple linear regression employed, it can be concluded that attitude, belief and knowledge are the significant contributor for acceptance towards contract farming. Conclusion/Recommendation: It is recommended that more studies can be conducted to inspect the complexities related with youths participation in contract farming and special attention should be highlighted to identify what universities can do in strategizing specific agricultural courses that would motivate youth to possess a better acceptance towards contract farming.